Development of Transverse Tubular Systems (T-Tubules) in the Hamster {Mesocricetus Auratus) Myocardium. - Adjenti, S.K. (University of Ghana, 2003)
With the aid of an electron microscope the development of transverse tubules (T-tubules or system) was studied in pre- and post-natal hamsters (Mesocricetus auratus) labelled with horse radish peroxidase (HRP). Thin sections (70-90 nm) and semi-thin sections (800-1000 nm) were cut using an ultramicrotome and examined under an electron microscope. No evidence of T-tubules was observed during the pre-natal and first week in neonatal stages of development when myocytes were characterised by large cytoplasmic spaces with few and partially developed but functioning myofibrils. Between seven and fourteen days of postnatal life, myofibrils developed rapidly and the A-and I-bands became more distinct. By the seventh day, shallow indentations of the sarcolemma at the Z-line regions appeared, representing the early beginnings of the T-system. Wide T-tubule invaginations of the sarcolemma with cross-sectional diameter of 200-205 nm began to appear in right and left ventricular myocytes by the twenty-first day of post-natal life in some Z-line regions of myofibrils. At this stage also, myofibrils had adopted adult forms, with well organised cross-striations. Mitochondria were also well developed, occupying the spaces between rows of myofibrils. University of Ghana http://ugspace.ug.edu.gh This study supports the view that T-tubules are primarily adapted for homeostatic functions of the mammalian cardiac myocytes, improving efficiency of transport of metabolic substrates and products, and that they are not for excitationcontraction coupling as presumed by some workers. It also shows that the wide T-system observed in the studies of myocytes of an adult hamster is pre-determined, as this feature is noticeable as early as the third week of post-natal development, coinciding with maturation of the myofibrils for active adult life.
Thesis (MPhil) - University of Ghana, 2003